CURRENT BIOPLASTIC FILM PRODUCTIONS DERIVED FROM AVOCADO (Persea americana Mill.) WASTE: A MINI-REVIEW - Truong Thi Dieu Hien; Tran Thi Ngoc Mai; Nguyen Thi Tra Mi (HUIT Journal of Science, 2025)
Avocado (Persea americana Mill.) is one of most favorite fruits for Vietnamese and along with consumption, the large amount of avocado waste is releasing and contributing significantly to environmental pollution. Recently, scientific reports indicated that avocado waste including seeds and peels contains starch, cellulose and antioxidants, which are useful to generate biofilms. Many studies have been implemented to figure out starch isolation methodologies and characterization from avocado seeds, and the additives to enhance biofilm performance such as plasticizers, fillers like chitosan, cellulose, etc. Moreover, avocado peel is also used for biofilm formation and exhibits some impressive results. These biofilms also verified their biodegradability within a short period of time, approximately 30 days after landfilling. Therefore, in this review, we summarize the methodologies of avocado seed starch isolation and corresponding biofilms quality assessment in presences of additives, including mechanical properties and biodegradability. This review would be a considerable reference to leverage avocado waste, an abandoned bioplastic-input source, aiming to deflate manufacturing cost in green-plastic production.